Intraoperative measurement of pressure gradient in median arcuate ligament syndrome as a rationale for radical surgical approach. Issue 1 (2nd January 2018) - Grus, Tomas; Lambert, Lukas; Vidim, Tomas; Grusova, Gabriela; Klika, Tomas
Abstract: Background: Median arcuate ligament syndrome (MALS) describes clinical symptoms in patients with stenosis of the celiac artery due to external compression by the ligament. There is an ongoing debate, whether sole release of the median arcuate ligament warrants long-term relief of the symptoms. Materials and methods: Eight patients diagnosed with MALS underwent open surgical treatment beginning with the release of the ligament. Systemic pressure and pressure in the left gastric artery were measured before and after division of the median arcuate ligament and release of the celiac artery. In patients with persistent gradient above 15 mm Hg after the release a PTFE bypass was performed. Results: After the release, the pressure gradient decreased from 66 ± 19 to 48 ± 14 mm Hg ( p  = .001) and therefore in all patients either an aorto-celiac bypass ( n  = 6) or aorto-hepatic bypass ( n  = 2) was created. Consequently, the gradient decreased to 7 ± 2 mm Hg ( p  = .0001). One month postoperatively, three patients were free of symptoms and the rest reported relief of symptoms. Conclusions: Release of the celiac artery resulted in insufficient decrease of pressure gradient, which was achieved by bypassing the segment with favorable mid-term outcome. We believe that the effect of the release should always be assessed to decide on subsequent treatment.